Anomalous Reflection from Phase Gradient Metasurfaces for Arbitrary Incident Angles - Odendaal, J.W. (Johann Wilhelm) (University of Pretoria, 2023)
Dissertation (MEng (Electronic Engineering))--University of Pretoria, 2023.